26 mu Fe-Si-Al magnetic powder core and preparation method thereof

Aerosolized iron-silicon aluminum alloy powder is prepared by high-pressure nitrogen atomization, and the powder resin and resin coating are used to combine nano-oxides to solve the problems of unenvironmental protection and low coating efficiency in the prior art. , realizes efficient preparation of ferrosilicon aluminum magnetic powder core, with low magnetic permeability, good electrical properties and mechanical strength.

CN119230276APending Publication Date: 2024-12-31ZHEJIANG KEDA MAGNETOELECTRICITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411422903.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The use of chemical passivating agents in the existing preparation method of ferrosilicon aluminum magnetic powder core is not environmentally friendly, the powder yield is low, and the slag powder is produced by insulating coating. The compression of the coated particles is large during the pressing process, which is not conducive to mold release and loss. The superposition characteristics of DC are poor.

Method used

Aerosolized iron-silicon aluminum alloy powder is prepared by high-pressure nitrogen atomization, and a cladding layer is formed by annealing of powder resin. Silane and silicone oil are used as intermediate layers, combined with silicone resin and epoxy resin to coat, and introduced during the pressing process. Nanooxides avoid chemical passivators and improve coating efficiency and mechanical strength.

Benefits of technology

Chemically-free passivator coating is achieved, powder yield and mechanical strength is improved, magnetic permeability and eddy current loss is reduced, compressive density and molding effect are improved, and powder yield can reach more than 96% during the coating process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005081345270000061
    Figure BDA0005081345270000061
Patent Text Reader

Abstract

The invention discloses a 26 mu Fe-Si-Al magnetic powder core and a preparation method thereof, and the preparation method comprises the following specific steps: S1, proportioning, smelting and casting iron blocks, aluminum blocks and silicon blocks, performing gas atomization to obtain gas atomized Fe-Si-Al alloy powder, and performing grain size distribution to obtain a mixed magnetic powder core; s2, uniformly mixing powder resin with the mixed magnetic powder core in the S1, and annealing to obtain annealed powder; s3, an ethanol dispersion liquid of silane and silicone oil is poured into the annealed powder obtained in the S2, baking is conducted after even mixing, and first baked powder is obtained; s4, organic silicon resin acetone dispersion liquid and / or epoxy resin acetone dispersion liquid are / is added into the first baked powder obtained in the S3, the mixture is evenly mixed and then baked, and second baked powder is obtained; s5, carrying out compression molding; s6, annealing and sintering; and S7, a coating is sprayed on the surface, and a finished iron-silicon-aluminum magnetic powder core product is obtained. According to the scheme, the Fe-Si-Al magnetic powder core with the magnetic conductivity being about 26 mu, the magnetic core loss being lower than 1400 mW / cm < 3 > and the powder yield being higher than 96% can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of metal soft magnetism, and in particular to a 26μ Sendust magnetic powder core and a preparation method thereof. Background Art

[0002] Sendust magnetic powder core has the advantages of high resistivity, relatively high saturation magnetic induction intensity, low coercive force, low loss, etc. The magnetocrystalline anisotropy constant and magnetostriction coefficient are both close to 0. The noise at different operating frequencies is small. It has excellent comprehensive soft magnetic properties and is widely used in electronic components such as filters, boost inductors and differential mode inductors.

[0003] Sendust aluminum alloy powder is usually prepared by two methods: crushing and gas atomization. The powder prepared by the crushing method is usually in irregular flake shape, with a simple preparation process, low cost, and good forming, but poor loss and DC superposition characteristics. The sendust aluminum powder prepared by the gas atomization method is spherical in shape, with low loss and excellent DC superposition characteristics.

[0004] Low magnetic permeability Sendust magnetic powder cores are usually obtained by insulating and coating the outer surface of Sendust alloy powder, and then insulating and pressing the metal alloy powder after the insulation coating. During the insulation coating process, a large amount of chemical passivating agent is usually introduced to react on the surface of the metal particles to form a thick insulating layer. For example, a patent application with publication number CN114724833A discloses a method for preparing ultra-low magnetic permeability aerosolized Sendust magnetic powder cores, a method for preparing lead or chromium-containing Sendust powder by aerosolization is invented, and a passivation coating method of a mixed solution of phosphoric acid, hydrochloric acid and boric acid is proposed, wherein the passivation coating liquid is boric acid, An appropriate amount of chromic acid is added to the mixed acid solution formed by mixing hydrochloric acid and water. The mixed acid solution can thicken the coating of the insulating layer. In addition, the lead or chromium introduced by smelting in the sendust powder can improve the uniformity of the oxide film covering the surface of the sendust powder. The patent application with publication number CN104505208A discloses a preparation method of a low-loss high-overlap sendust material with a magnetic permeability μ=26. The method comprises powder proportioning, phosphating, one-time annealing, and then adding a high-temperature resistant insulating material, and then pressing and annealing to obtain a 26μ sendust magnetic core, and the loss is close to 700mW / cm at 100kHz / 100mT. 3 However, chemical passivators are not environmentally friendly, and react violently during the coating process, resulting in a low powder yield. Insulation coating produces a lot of slag powder. During the pressing process, the compression of the coated particles is relatively large, which is not conducive to pressing and demolding. Summary of the invention

[0005] In order to solve the problems involved in the background technology, the present invention provides a 26μ Sendust magnetic powder core and a preparation method thereof. The preparation method does not use a chemical passivator, has a high coating powder yield, and the Sendust magnetic powder core prepared by the method has low magnetic permeability while having good electrical properties and mechanical strength.

[0006] The present invention provides a method for preparing a 26μ Sendust magnetic powder core, and the specific steps are as follows:

[0007] S1: iron block, aluminum block and silicon block are mixed according to the following mass percentages: Si 9.5%-9.7%, Al 5.2%-5.4%, and the rest is Fe; the three are placed in a vacuum furnace for smelting and casting, and atomized by high-pressure nitrogen to obtain gas-atomized iron-silicon-aluminum alloy powder, and the gas-atomized iron-silicon-aluminum alloy powder is obtained by particle size grading to obtain a mixed magnetic powder core;

[0008] S2: Evenly mix the powder resin and the mixed magnetic powder core in S1, and anneal in an inert atmosphere to obtain annealed powder;

[0009] S3: pouring ethanol dispersion of silane and silicone oil into the annealed powder obtained in S2, mixing evenly and then baking to obtain baked powder 1;

[0010] S4: adding a silicone resin acetone dispersion and / or an epoxy resin acetone dispersion to the baked powder 1 obtained in S3, mixing well and then baking to obtain a baked powder 2;

[0011] S5: adding a release agent and nano-oxide to the baked powder obtained in S4, mixing them evenly, and pressing them into a magnetic powder core blank using a hydraulic press;

[0012] S6: annealing the magnetic powder core blank pressed and formed in S5 under the protection of an inert or reducing gas to obtain a semi-finished magnetic powder core;

[0013] S7: Spray a layer of epoxy resin coating on the surface of the semi-finished magnetic powder core of S6 to obtain a finished Sendust magnetic powder core.

[0014] Preferably, in S1, the particle size of the mixed magnetic powder core and its weight parts include: -350 to +500 mesh 65 to 75 parts, -500 to +800 mesh 15 to 25 parts, -800 mesh 10 to 20 parts.

[0015] Preferably, in S2, the powder resin is one or more of silicone resin, epoxy resin and phenolic resin, the particle size of the powder resin is 5 to 10 μm, and the mass ratio of the powder resin to the mixed magnetic powder core is 1.0 to 2.5:100.

[0016] Preferably, in S2, the inert gas is nitrogen or argon, the annealing temperature is 850-950° C., and the holding time is 1-2 h.

[0017] Preferably, in S3, the mass ratio of annealing powder, silane, silicone oil and ethanol is 100:0.2-1:0.1-0.3:20-40. After mixing, the four are stirred for 10 minutes and baked at 80-150°C for 30-60 minutes to obtain baked powder one.

[0018] Preferably, in S4, the mass ratio of baking powder 1, silicone resin and / or epoxy resin and acetone is 100:1-2:6-7. After mixing, the three are stirred for 10 minutes and baked at 80-150°C for 30-60 minutes to obtain baking powder 2.

[0019] Preferably, in S5, the release agent is one or more of zinc stearate, calcium stearate and molybdenum disulfide, the nano-oxide is one or more of SiO2, Al2O3, ZrO2 and TiO2, wherein the particle size of the nano-oxide is 5000-7000 mesh, the specific surface area of ​​the nano-oxide is 190-210m2 / g, and the mass ratio of the baked powder 2, the release agent and the nano-oxide is 100:0.3-0.5:0.2-0.4.

[0020] Preferably, in S5, the molding pressure of the hydraulic press is 17 to 21 t·cm-2, and the density of the magnetic powder core blank is 5.5 to 6.0 g·cm-3.

[0021] Preferably, in S6, the annealing heat treatment atmosphere is a nitrogen atmosphere, the annealing heating rate is 10-20°C / min, the maximum holding temperature is 680-800°C, the holding time is 1-2.5h, and then cooled to room temperature to obtain a semi-finished magnetic powder core.

[0022] A 26μ Sendust magnetic powder core manufactured by the manufacturing method as described above.

[0023] The beneficial effects of the present invention are:

[0024] 1. The present invention forms a primary coating on the mixed magnetic powder core by annealing the powder resin at high temperature, uses silane and silicone oil as the coating intermediate layer, connects the outermost coated silicone resin and / or epoxy resin, and forms a tight coating layer structure outside the magnetic powder core, which can effectively reduce the magnetic permeability of the sendust magnetic powder core and effectively suppress eddy current loss; in the step of pressing and demolding, nano-scale oxides such as SiO2, Al2O3, ZrO2 and TiO2 are introduced to ensure that the surface of the sendust magnetic powder core that is not completely coated by the insulating material is more evenly coated. Different from the prior art that uses a large amount of passivation liquid such as phosphoric acid for insulation coating, in the present invention, no chemical passivator is used for insulation coating on the outside of the sendust magnetic powder core, and the powder yield during the coating process is significantly improved.

[0025] 2. In the present invention, the aerosolized iron silicon aluminum alloy powder adopts a three-level particle grading, an appropriate amount of secondary powder and tertiary fine powder are added to the coarse powder, and nano-scale oxides are introduced in the pressing and demolding steps. According to the particle close packing theory, the density in the pressing process can be effectively improved, and small-particle powder can be filled in the coarse powder, which is beneficial to compression molding and improves the mechanical strength of the magnetic powder core. DETAILED DESCRIPTION

[0026] The present invention is explained in detail below in conjunction with specific implementation cases:

[0027] Embodiment 1:

[0028] In this embodiment, a method for preparing a 26μ Sendust magnetic powder core is provided, and the specific steps are as follows:

[0029] S1: iron block, aluminum block and silicon block are mixed with the following mass percentages: Si 9.6%, Al 5.3%, Fe85.1%, and placed in a vacuum furnace for smelting. The three are placed in a vacuum furnace for smelting and casting, and atomized by high-pressure nitrogen to obtain gas-atomized iron-silicon-aluminum alloy powder. The gas-atomized iron-silicon-aluminum alloy powder is obtained by particle size grading to obtain a mixed magnetic powder core. The particle size and weight ratio of the mixed magnetic powder core include: -350 to +500 mesh 55 parts, -500 to +800 mesh 25 parts, -800 mesh 20 parts;

[0030] S2: The mixed magnetic powder core and the powdered silicone resin in S1 are mixed evenly, and annealed at 900°C for 60 minutes under nitrogen protection to obtain annealed powder; wherein the mass ratio of the powdered silicone resin to the mixed magnetic powder core is 1.5:100, and the particle size of the powdered silicone resin is 5 to 10 μm;

[0031] S3: Disperse 0.5% silane and 0.2% silicone oil in 30% ethanol, then pour the above dispersion into the annealed powder in S2, stir for 10 minutes, and bake at 100°C for 30 minutes to obtain baked powder 1;

[0032] S4: adding the organic silicone resin to acetone, stirring for 5 minutes to obtain an organic silicone resin acetone dispersion, then pouring the dispersion into the baking powder 1 in S3, stirring for 10 minutes, and baking at 100° C. for 30 minutes to obtain baking powder 2; wherein the mass ratio of baking powder 1, organic silicone resin and acetone is 100:1:6;

[0033] S5: 0.3% zinc stearate and 0.2% Al2O3 are mixed with the baked powder obtained in S4, wherein the Al2O3 particle size is 5000-7000 mesh and the specific surface area is 190-210m 2 / g, through hydraulic press 20t·cm -2 The compression molding pressure is 5.6 g·cm-3 Magnetic powder core blanks;

[0034] S6: subjecting the magnetic powder core blank to a heat treatment atmosphere of nitrogen, an annealing heating rate of 10°C / min, and a heat preservation temperature of 700°C for 1.5h, and then cooling to room temperature to obtain a semi-finished magnetic powder core;

[0035] S7: Spray a layer of epoxy resin coating on the surface of the semi-finished magnetic powder core of S6 to obtain a finished Sendust magnetic powder core.

[0036] Embodiment 2:

[0037] In this embodiment, a method for preparing a 26μ Sendust magnetic powder core is provided, and the specific steps are as follows:

[0038] S1: iron block, aluminum block and silicon block are mixed with the following mass percentages: Si 9.6%, Al 5.3%, Fe85.1%, and placed in a vacuum furnace for smelting. The three are placed in a vacuum furnace for smelting and casting, and atomized by high-pressure nitrogen to obtain gas-atomized iron-silicon-aluminum alloy powder. The gas-atomized iron-silicon-aluminum alloy powder is obtained by particle size grading to obtain a mixed magnetic powder core. The particle size and weight ratio of the mixed magnetic powder core include: -350 to +500 mesh 65 parts, -500 to +800 mesh 15 parts, -800 mesh 20 parts;

[0039] S2: The mixed magnetic powder core and the powdered silicone resin in S1 are mixed evenly, and annealed at 900°C for 60 minutes under nitrogen protection to obtain annealed powder; wherein the mass ratio of the powdered silicone resin to the mixed magnetic powder core is 1.5:100, and the particle size of the powdered silicone resin is 5 to 10 μm;

[0040] S3: Disperse 0.5% silane and 0.2% silicone oil in 30% ethanol, then pour the above dispersion into the annealed powder in S2, stir for 10 minutes, and bake at 100°C for 30 minutes to obtain baked powder 1;

[0041] S4: adding the organic silicone resin to acetone, stirring for 5 minutes to obtain an organic silicone resin acetone dispersion, then pouring the dispersion into the baking powder 1 in S3, stirring for 10 minutes, and baking at 100° C. for 30 minutes to obtain baking powder 2; wherein the mass ratio of baking powder 1, organic silicone resin and acetone is 100:1:6;

[0042] S5: 0.3% zinc stearate and 0.2% Al2O3 are mixed with the baked powder obtained in S4, wherein the Al2O3 particle size is 5000-7000 mesh and the specific surface area is 190-210m 2 / g, through hydraulic press 20t·cm -2 The compression molding pressure is 5.6 g·cm -3 Magnetic powder core blanks;

[0043] S6: subjecting the magnetic powder core blank to a heat treatment atmosphere of nitrogen, an annealing heating rate of 10°C / min, and a heat preservation temperature of 700°C for 1.5h, and then cooling to room temperature to obtain a semi-finished magnetic powder core;

[0044] S7: Spray a layer of epoxy resin coating on the surface of the semi-finished magnetic powder core of S6 to obtain a finished Sendust magnetic powder core.

[0045] Embodiment 3:

[0046] In this embodiment, a method for preparing a 26μ Sendust magnetic powder core is provided, and the specific steps are as follows:

[0047] S1: iron block, aluminum block and silicon block are mixed with the following mass percentages: Si 9.6%, Al 5.3%, Fe85.1%, and placed in a vacuum furnace for smelting. The three are placed in a vacuum furnace for smelting and casting, and atomized by high-pressure nitrogen to obtain gas-atomized iron-silicon-aluminum alloy powder. The gas-atomized iron-silicon-aluminum alloy powder is obtained by particle size grading to obtain a mixed magnetic powder core. The particle size and weight ratio of the mixed magnetic powder core include: -350 to +500 mesh 65 parts, -500 to +800 mesh 15 parts, -800 mesh 20 parts;

[0048] S2: the mixed magnetic powder core and powdered epoxy silicone resin in S1 are mixed evenly, and annealed at 850°C for 60 minutes under nitrogen protection to obtain annealed powder; wherein the mass ratio of powdered epoxy silicone resin to the mixed magnetic powder core is 1.5:100, and the particle size of the powdered resin is 5 to 10 μm;

[0049] S3: Disperse 0.5% silane and 0.2% silicone oil in 30% ethanol, then pour the above dispersion into the annealed powder in S2, stir for 10 minutes, and bake at 100°C for 30 minutes to obtain baked powder 1;

[0050] S4: adding the organic silicone resin to acetone, stirring for 5 minutes to obtain an organic silicone resin acetone dispersion, then pouring the dispersion into the baking powder 1 in S3, stirring for 10 minutes, and baking at 100° C. for 30 minutes to obtain baking powder 2; wherein the mass ratio of baking powder 1, organic silicone resin and acetone is 100:1:6;

[0051] S5: 0.3% zinc stearate and 0.2% Al2O3 are mixed with the baked powder obtained in S4, wherein the nano Al2O3 has a particle size of 5000-7000 mesh and a specific surface area of ​​190-210 m 2 / g, through hydraulic press 20t·cm -2 The compression molding pressure is 5.6 g·cm -3 Magnetic powder core blanks;

[0052] S6: subjecting the magnetic powder core blank to a heat treatment atmosphere of nitrogen, an annealing heating rate of 10°C / min, and a heat preservation temperature of 700°C for 1.5h, and then cooling to room temperature to obtain a semi-finished magnetic powder core;

[0053] S7: Spray a layer of epoxy resin coating on the surface of the semi-finished magnetic powder core of S6 to obtain a finished Sendust magnetic powder core.

[0054] Embodiment 4:

[0055] In this embodiment, a method for preparing a 26μ Sendust magnetic powder core is provided, and the specific steps are as follows:

[0056] S1: iron block, aluminum block and silicon block are mixed with the following mass percentages: Si 9.6%, Al 5.3%, Fe85.1%, and placed in a vacuum furnace for smelting. The three are placed in a vacuum furnace for smelting and casting, and atomized by high-pressure nitrogen to obtain gas-atomized iron-silicon-aluminum alloy powder. The gas-atomized iron-silicon-aluminum alloy powder is obtained by particle size grading to obtain a mixed magnetic powder core. The particle size and weight ratio of the mixed magnetic powder core include: -350 to +500 mesh 65 parts, -500 to +800 mesh 15 parts, -800 mesh 20 parts;

[0057] S2: The mixed magnetic powder core and the powdered silicone resin in S1 are uniformly mixed, and annealed at 850°C for 60 minutes under nitrogen protection to obtain annealed powder; wherein the mass ratio of the powdered silicone resin to the mixed magnetic powder core is 1.5:100, and the particle size of the powdered silicone resin is 5 to 10 μm;

[0058] S3: 1.0% silane and 0.3% silicone oil were dispersed in 30% ethanol, and then the dispersion was poured into the annealed powder in S2, stirred for 10 minutes, and baked at 100°C for 30 minutes to obtain baked powder 1;

[0059] S4: adding the organic silicone resin to acetone, stirring for 5 minutes to obtain an organic silicone resin acetone dispersion, then pouring the dispersion into the baking powder 1 in S3, stirring for 10 minutes, and baking at 100° C. for 30 minutes to obtain baking powder 2; wherein the mass ratio of baking powder 1, organic silicone resin and acetone is 100:1:6;

[0060] S5: 0.3% zinc stearate and 0.2% Al2O3 are mixed with the baked powder obtained in S4, wherein the nano Al2O3 has a particle size of 5000-7000 mesh and a specific surface area of ​​190-210 m 2 / g, through hydraulic press 20t·cm -2 The compression molding pressure is 5.6 g·cm -3 Magnetic powder core blanks;

[0061] S6: subjecting the magnetic powder core blank to a heat treatment atmosphere of nitrogen, an annealing heating rate of 10°C / min, and a heat preservation temperature of 700°C for 1.5h, and then cooling to room temperature to obtain a semi-finished magnetic powder core;

[0062] S7: Spray a layer of epoxy resin coating on the surface of the semi-finished magnetic powder core of S6 to obtain a finished Sendust magnetic powder core.

[0063] Embodiment 5:

[0064] In this embodiment, a method for preparing a 26μ Sendust magnetic powder core is provided, and the specific steps are as follows:

[0065] S1: iron block, aluminum block and silicon block are mixed with the following mass percentages: Si 9.6%, Al 5.3%, Fe85.1%, and placed in a vacuum furnace for smelting. The three are placed in a vacuum furnace for smelting and casting, and atomized by high-pressure nitrogen to obtain gas-atomized iron-silicon-aluminum alloy powder. The gas-atomized iron-silicon-aluminum alloy powder is obtained by particle size grading to obtain a mixed magnetic powder core. The particle size and weight ratio of the mixed magnetic powder core include: -350 to +500 mesh 55 parts, -500 to +800 mesh 25 parts, -800 mesh 20 parts;

[0066] S2: The mixed magnetic powder core and the powdered silicone resin in S1 are uniformly mixed, and annealed at 850°C for 60 minutes under nitrogen protection to obtain annealed powder; wherein the mass ratio of the powdered silicone resin to the mixed magnetic powder core is 1.5:100, and the particle size of the powdered silicone resin is 5 to 10 μm;

[0067] S3: Disperse 0.5% silane and 0.2% silicone oil in 30% ethanol, then pour the above dispersion into the annealed powder in S2, stir for 10 minutes, and bake at 100°C for 30 minutes to obtain baked powder 1;

[0068] S4: adding the organic silicone resin to acetone, stirring for 5 minutes to obtain an organic silicone resin acetone dispersion, then pouring the dispersion into the baking powder 1 in S3, stirring for 10 minutes, and baking at 100° C. for 30 minutes to obtain baking powder 2; wherein the mass ratio of baking powder 1, organic silicone resin and acetone is 100:1:6;

[0069] S5: 0.3% zinc stearate and 0.2% SiO2 are mixed with the baked powder obtained in S4, wherein the nano Al2O3 has a particle size of 5000-7000 mesh and a specific surface area of ​​190-210 m 2 / g, through hydraulic press 20t·cm -2 The compression molding pressure is 5.6 g·cm -3 Magnetic powder core blanks;

[0070] S6: subjecting the magnetic powder core blank to a heat treatment atmosphere of nitrogen, an annealing heating rate of 10°C / min, and a heat preservation temperature of 700°C for 1.5h, and then cooling to room temperature to obtain a semi-finished magnetic powder core;

[0071] S7: Spray a layer of epoxy resin coating on the surface of the semi-finished magnetic powder core of S6 to obtain a finished Sendust magnetic powder core.

[0072] The powder yields in the preparation process of the Sendust magnetic powder cores in Implementation Cases 1 to 5 were statistically calculated, and the performance of the finished Sendust magnetic powder cores was tested. The measured data are shown in Table 1 below.

[0073] Table 1: Magnetic permeability, core loss test data and powder yield statistics of Sendust magnetic powder cores of Examples 1 to 5

[0074]

[0075] It can be seen from Table 1 above that the mixed magnetic powder core is coated once by high-temperature annealing of silicone resin, epoxy resin or phenolic resin, silane and silicone oil are used as the coating intermediate layer, and the outermost coated silicone resin and / or epoxy resin are connected to form a tight coating layer structure outside the magnetic powder core, which can effectively reduce the magnetic permeability of the sendust magnetic powder core and effectively suppress eddy current loss; in the step of pressing and demolding, nano-scale oxides such as SiO2, Al2O3, ZrO2 and TiO2 are introduced to ensure that the surface of the sendust magnetic powder core that is not completely coated by the insulating material is more evenly coated, thereby obtaining a medium-high frequency and low-loss 26μ atomized sendust magnetic powder core, and the powder yield of the coating process can be as high as 96% or more.

[0076] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a 26μ Sendust magnetic powder core, characterized in that: The specific steps are as follows: S1: iron block, aluminum block and silicon block are mixed according to the following mass percentages: Si 9.5%-9.7%, Al 5.2%-5.4%, and the rest is Fe; the three are placed in a vacuum furnace for smelting and casting, and atomized by high-pressure nitrogen to obtain gas-atomized iron-silicon-aluminum alloy powder, and the gas-atomized iron-silicon-aluminum alloy powder is obtained by particle size grading to obtain a mixed magnetic powder core; S2: Evenly mix the powder resin and the mixed magnetic powder core in S1, and anneal in an inert atmosphere to obtain annealed powder; S3: pouring ethanol dispersion of silane and silicone oil into the annealed powder obtained in S2, mixing evenly and then baking to obtain baked powder 1; S4: adding a silicone resin acetone dispersion and / or an epoxy resin acetone dispersion to the baked powder 1 obtained in S3, mixing well and then baking to obtain a baked powder 2; S5: adding a release agent and nano-oxide to the baked powder obtained in S4, mixing them evenly, and pressing them into a magnetic powder core blank using a hydraulic press; S6: annealing the magnetic powder core blank pressed and formed in S5 under the protection of an inert or reducing gas to obtain a semi-finished magnetic powder core; S7: Spray a layer of epoxy resin coating on the surface of the semi-finished magnetic powder core of S6 to obtain a finished Sendust magnetic powder core.

2. The method for preparing a 26μ Sendust magnetic powder core according to claim 1, characterized in that: In S1, the particle size of the mixed magnetic powder core and its weight parts include: -350 to +500 mesh 65 to 75 parts, -500 to +800 mesh 15 to 25 parts, -800 mesh 10 to 20 parts.

3. The method for preparing a 26μ Sendust magnetic powder core according to claim 1, characterized in that: In S2, the powder resin is one or more of silicone resin, epoxy resin and phenolic resin, the particle size of the powder resin is 5 to 10 μm, and the mass ratio of the powder resin to the mixed magnetic powder core is 1.0 to 2.5:

100.

4. The method for preparing a 26μ Sendust magnetic powder core according to claim 1, characterized in that: In S2, the inert gas is nitrogen or argon, the annealing temperature is 850-950°C, and the holding time is 1-2h.

5. The method for preparing a 26μ Sendust magnetic powder core according to claim 1, characterized in that: In S3, the mass ratio of annealing powder, silane, silicone oil and ethanol is 100:0.2-1:0.1-0.3:20-40. After mixing, the four are stirred for 10 minutes and baked at 80-150°C for 30-60 minutes to obtain baked powder one.

6. The method for preparing a 26μ Sendust magnetic powder core according to claim 1, characterized in that: In S4, the mass ratio of baking powder 1, silicone resin and / or epoxy resin and acetone is 100:1-2:6-7. After the three are mixed, they are stirred for 10 minutes and baked at 80-150° C. for 30-60 minutes to obtain baking powder 2.

7. The method for preparing a 26μ Sendust magnetic powder core according to claim 1, characterized in that: In S5, the release agent is one or more of zinc stearate, calcium stearate and molybdenum disulfide, the nano oxide is one or more of SiO2, Al2O3, ZrO2 and TiO2, wherein the particle size of the nano oxide is 5000-7000 mesh, and the specific surface area of ​​the nano oxide is 190-210m 2 / g, the mass ratio of the baked powder 2, the release agent and the nano oxide is 100: 0.3-0.5: 0.2-0.

4.

8. The method for preparing a 26μ Sendust magnetic powder core according to claim 1, characterized in that: In S5, the hydraulic press molding pressure is 17 to 21 t·cm -2 The density of the magnetic powder core blank is 5.5~6.0g·cm -3 .

9. The method for preparing a 26μ Sendust magnetic powder core according to claim 1, characterized in that: In S6, the annealing heat treatment atmosphere is a nitrogen atmosphere, the annealing heating rate is 10-20°C / min, the maximum holding temperature is 680-800°C, the holding time is 1-2.5h, and then cooled to room temperature to obtain a semi-finished magnetic powder core.

10. A 26μ Sendust magnetic powder core made by the preparation method according to any one of claims 1 to 9.